ANALISIS PENGGUNAAN ALIH KODE DALAM KOMUNIKASI PEMASARAN DI INSTAGRAM: STUDI KASUS BURJO NGEGAS SEMARANG - Cicha Olivia Nauri; Dewi Sintya Sari; Putri Qurrota A’yuni; Ana Putri Nastiti (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the forms and functions of code switching in marketing communication on the Instagram account @burjongegas Semarang. This research employs a descriptive qualitative method, with promotional Instagram content including captions, photos, videos, Reels, and Stories, as the object of analysis. Data were collected through observation and case study, then analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the @burjongegas Instagram account uses two types of code switching: (a) Internal code switching (between Indonesian and Javanese) and (b) external code switching (involving Indonesian, English, and Javanese). The use of Javanese helps create a sense of closeness with the audience while reinforcing the brand’s local identity. Meanwhile, English is used to enhance the attractiveness of promotional contents. These findings indicate that code switching serves not only as a form of linguistic variation but also as an effective digital marketing communication strategy for attracting audience attention.